Molecular identification of sharks and rays species from Aceh waters, Indonesia - Mutia Ramadhaniaty; Maria Ulfah; Indra Indra; Nur Fadli; Nanda Muhammad Razi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Shark is a cartilaginous fish that is widely hunted because it has high economic value. The waters of Aceh are directly adjacent to the Indian Ocean and the Malacca Strait making it a preferred habitat for pelagic fish, especially sharks. Information on shark species landed in the waters west and east of Aceh is very limited due to difficulties in identification and commonly used local names. This study aimed to determine the types of sharks landed in Banda Aceh, Meulaboh, Langsa, Southwest Aceh and Simeulu and to find out specifically what species of sharks are most often landed in Aceh waters. Primary data gathering consisted of four stages, namely sample collection, identification using identification books, molecular identification cytochrome oxidase subunit I (COI) and phylogenetic analysis. The results of the molecular analysis of 46 tissue samples from five locations identified 13 species of sharks, namely Carcharhinhus sorrah, Carcharhinhus amboinensis, Triaenodon obesus, Isurus oxyrinchus, Sphyrna zygaena, Sphyrna lewini, Loxodon macrorhinus, Hemipristis elongaria, Stagostoma fasciatum, Nebrius ferrugineus, Chilloscyllium punctatum, Isurus oxyrinchus, Alopias pelagicus, Alopias supercillosus and 1 species of rays, namely Rhynchobatus australiae. Phylogenetic tree reconstruction using the Neighbor Joining method of 610 basepairs consisting of two large clades separates the species Alopias pelagicus and Isurus oxyrichus with Carcharhinus sorrah, Sphyrna lewini, Loxodon macrorhinus and Rhyncobatus australiae with boostrap values of 87% and 64%. The haplotype diversity shown ranged from 0.667-0.889 while the nucleotide diversity ranged from 0.001-0.097. These values indicates high diversity because of the variance in the number of species found.Keywords:BarcodeCOISharks catchAlopias supercillosusSphyrna lewini